Pengaruh Trietanolamin terhadap Karakteristik Fisika Kimia dan Laju Pelepasan Ibuprofen dalam Sediaan Gel Dispersi Padat Ibuprofen-PEG 6000 (Effect of Triethanolamine on Physicochemical Characteristic and Dissolution Rate of Ibuprofen in Ibuprofen-PEG 600 - Tanfidz Alishlah; Budipratiwi Wisudyaningsih; Lidya Ameliana (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
The present research has been undertaken with the aim to develop a topical gel formulation of ibuprofen which would avoid side effects of ibuprofen in oral administration. In this study, ibuprofen was made in solid dispersion form with PEG 6000 polymer composition 1 : 1.5 by fusion method. Solid dispersions aims to improve the solubility of ibuprofen. Triethanolamine as an alkalizing agent was added with different concentration in each gel formula which are 1 %, 2 %, and 4 %. They were evaluated for physicochemical properties such as organoleptic, pH, viscosity and in vitro drug release. Based on this research, it can be concluded that the different concentration of triethanolamine doesn’t give the significant effect on viscosity, nonetheless there is a significant effect on pH and dissolution rate of ibuprofen. It is obtained that the highest dissolution rate is F3 with a flux as 216.93 μg/cm2.minutes. Keywords: gel, ibuprofen, solid dispersion, PEG 6000, triethanolamine